Daily Report from the California Democratic Delegation (1968)
This August 24, 1968 "Daily Report" from the California Democratic Delegation outlines scheduled events and activities during the Democratic National Convention week in Chicago. It provides a day-by-day calendar from August 25–29, including caucuses, receptions, teas, luncheons, women's events, hospitality suites, and convention sessions, many held at the La Salle Hotel, Conrad Hilton, and Sheraton Blackstone. The report highlights special events honoring delegation members, appearances by political figures and candidates, and organized gatherings such as "Food for Thought" luncheons and women's committee functions. It also lists hospitality centers for supporters of McCarthy, McGovern, and Humphrey, along with contact information for women's activities within the California delegation. The document serves as a logistical guide to help delegates coordinate participation in political, social, and campaign-related events throughout the convention.